Effects of Buddhist Doctrine Based Practice on Fear of Cancer Recurrence and Hopelessness Among Breast Cancer Survivors - Benyaporn Bannaasan (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Fear of cancer recurrence and hopelessness are major psychological problems found after completion of primary treatment among breast cancer survivors and these feelings can affect their quality of life. This randomized control trial aimed to examine the effectiveness of the Buddhist Doctrine Based Practice in reducing fear of cancer recurrence and hopelessness. A sample of 59 breast cancer survivors, who received primary treatment only, who were 1 to 3 years post-diagnosis and cancer-free, and who met the inclusion criteria were recruited. Participants were randomly assigned into the experimental group and the control group; 29 in the experimental group and 30 in the control group. The experimental group received a 9-day intervention consisting of three sessions of group education and 8 days of self-training in critical reflection, while the control group received usual care. Data were collected using the Concerns about Recurrence Scale (CARS) and the Beck Hopelessness Scale (BHS) before the intervention, immediately following the intervention, as well as 2 weeks and 1 month following the intervention. All instruments were tested for validity and reliability which were at an acceptable level. Data were analyzed using descriptive statistics, the Friedman test, and Mann-Whitney U test. Results indicated that breast cancer survivors receiving the Buddhist Doctrine Based Practice had lower fear of cancer recurrence following the intervention than they had before the intervention at all points of measurement (p < .001). There was a significant difference in fear of cancer recurrence between the two groups at 2 weeks and 1 month after finishing the intervention (p < .05). Additionally, the results demonstrated that breast cancer survivors receiving the Buddhist Doctrine Based Practice had lower hopelessness following the intervention than before the intervention at all points of measurement (p < .001). There was a significant difference in hopelessness between the two groups at 1 month after finishing the intervention (p < .05). The findings imply that nurses can use the Buddhist Doctrine Based Practice to reduce fear of cancer recurrence and hopelessness among breast cancer survivors after completion of primary treatment. Further study should be performed with longer duration to assess the long-term impact of the intervention and should explore in a qualitative study among breast cancer survivors whose sufferings were reduced by the program used in this study to reveal the process of cognitive change.